Systematic review and network meta‐analysis: efficacy of licensed drugs for abdominal bloating in irritable bowel syndrome with constipation. Issue 2 (11th June 2021) - Nelson, Alfred D.; Black, Christopher J.; Houghton, Lesley A.; Lugo‐Fagundo, Nahyr Sofía; Lacy, Brian E.; Ford, Alexander C.
Summary: Background: Although bloating is a highly prevalent and troublesome symptom in irritable bowel syndrome with constipation (IBS‐C), treatment is empirical with no specific guidelines for its management. Aim: To conduct a pairwise and network meta‐analysis, using a frequentist approach, of Food and Drug Administration‐licensed drugs for IBS‐C comparing their efficacy for abdominal bloating as a specific endpoint. Methods: We searched the medical literature through December 2020 to identify randomised controlled trials (RCTs) in IBS‐C, with abdominal bloating reported as a dichotomous assessment. Efficacy of each drug was reported as a pooled relative risk (RR) with 95% confidence intervals (CIs) to summarise effect of each comparison tested. Treatments were ranked according to their P ‐score. Results: We identified 13 eligible RCTs, containing 10 091 patients. Linaclotide 290 µg o.d., lubiprostone 8 µg b.d., tenapanor 50 mg b.d. and tegaserod 6 mg b.d. were all superior to placebo for abdominal bloating in patients with IBS‐C, in both pairwise and the network meta‐analyses. Linaclotide demonstrated the greatest improvement in abdominal bloating in both pairwise and network meta‐analysis (RR of failure to achieve an improvement in abdominal bloating = 0.78; 95% CI 0.74‐0.83, number needed to treat = 7, P ‐score 0.97). Indirect comparison revealed no significant differences between individual drugs. Conclusions: We found all licensed drugs for IBS‐C to be superior to placebo for abdominal bloating. Linaclotide appeared to be the most efficacious at relieving abdominal bloating. Further research is needed to assess long‐term efficacy of these agents and to better understand the precise mechanism of improving bloating. Abstract : Linaclotide, lubiprostone, tegaserod, and tenapanor were all more efficacious than placebo, with linaclotide 290 µg o.d. ranked as the most efficacious treatment (RR = 0.78; 95% CI 0.74‐0.83, P ‐score 0.97).